Novel cobalt-doped molybdenum oxynitride quantum dot@N-doped carbon nanosheets with abundant oxygen vacancies for long-life rechargeable zinc–air batteries. Issue 14 (23rd March 2021) - Nguyen, Thanh Tuan; Balamurugan, Jayaraman; Lau, Kin-Tak; Kim, Nam Hoon; Lee, Joong Hee
Abstract : A novel cobalt-doped molybdenum oxynitride quantum dot@N-doped carbon nanosheets with abundant oxygen vacancies have been established. The optimal VO -CMON@NCN air-cathode achieved tremendous peak power density and ultralong cycle life for 500 h. Abstract : Rechargeable zinc–air batteries (ZABs) have emerged as promising alternatives for conventional Li-ion batteries due to their high energy density and low manufacturing cost. However, Pt/C and RuO2 -based conventional rechargeable ZABs are mainly constrained by the sluggish kinetics of oxygen reduction/oxygen evolution reactions (ORR/OER), limiting commercialization possibilities. Herein, a new type of oxygen vacancies enriched cobalt-doped molybdenum oxynitride quantum dot-anchored N-doped carbon nanosheets (VO -CMON@NCNs) was demonstrated as an advanced air-cathode for long-life rechargeable ZABs. Such VO -CMON@NCN catalyst has an exceptional ORR performance with a high half-wave potential of 0.857 V and tremendous OER performance with an ultrasmall overpotential of 240 mV at a current density of 10 mA cm −2, outperforming conventional Pt/C and RuO2 catalysts. As proof of concept, rechargeable ZABs with an optimal VO -CMON@NCN-800 air-cathode showed an ultrahigh specific capacity of 721.2 mA h gZn −1 at a current density of 5 mA cm −2, a tremendous peak power density of 143.7 mW cm −2, and ultralong cycling life of 500 h. These consequences suggest that the oxygen vacancies enriched VO -CMON@NCN can serve as promising bifunctional catalysts for next-generation metal–air batteries and other energy-related applications.